2022
DOI: 10.1088/2058-8585/ac7bc3
|View full text |Cite
|
Sign up to set email alerts
|

An electromagnetic shield design using frequency selective surfaces on a textile substrate

Abstract: In this paper, a flexible bandstop frequency selective surface (FSS) array fabricated on jeans substrate using silver-coated conductive yarn with a computerized embroidery machine is presented for X-band. The S parameters of the fabricated design are measured through the free space method. The measured S-parameters showed significant stopband characteristics between 8 GHz-11.5 GHz for -30o to 30o degrees wide incident angles. Moreover, the transmission, reflection, absorption, and shielding effectiveness (SE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Therefore, FSFs can be prepared by increasing the conductivity of the embroidery yarn and using periodic embroidery patterns. 26,27 Noaman Naseer 28 et al prepared a flexible band-stop FSS array for X-band on jeans substrate by using silver-coated conductive yarn and computer embroidery machine. The results showed that the prototype provides more than 30 dB SE in the X-band and has main absorption behavior for some frequencies in the band.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, FSFs can be prepared by increasing the conductivity of the embroidery yarn and using periodic embroidery patterns. 26,27 Noaman Naseer 28 et al prepared a flexible band-stop FSS array for X-band on jeans substrate by using silver-coated conductive yarn and computer embroidery machine. The results showed that the prototype provides more than 30 dB SE in the X-band and has main absorption behavior for some frequencies in the band.…”
Section: Introductionmentioning
confidence: 99%